KEAHLIAN PEMAKAI SEBAGAI PEMODERASI PENGARUH PERCEIVED USEFULNESS DAN PARTISIPASI TERHADAP KEPUASAN DALAM PENGEMBANGAN SISTEM INFORMASI - ratna, Ganis Kutha; Dharmadiaksa, Ida Bagus (E-Jurnal Akuntansi, 2017)
This study aimed to examine the effect of perceived usefulness and participation on satisfaction and the ability of the user expertise to moderate the influence of perceived usefulness and the satisfaction of participation in the development of information systems. Samples of this study 51 people obtained by purposive sampling technique. Data analysis technique used is multiple regression analysis and test Moderating Regression Analysis. The research data qualifies that the normal distribution of data and models used do not contain any heteroscedasticity. The first hypothesis testing results prove that the variables perceived usefulness significant positive effect on satisfaction. The second hypothesis testing results prove positive and significant participation of the third hypothesis. Provide results that user expertise moderating effect of perceived usefulness to satisfaction in system development. The fourth hypothesis testing provides results that user expertise moderating influence on satisfaction of participation in the development of information systems
Keywords: perceived usefulness, participation, satisfaction, user expertise, information systems development